Living at the edge: home range patterns of the Buraiga Chimpanzee Community, Kibale National Park, Uganda - Edwards, Wren I.; Popescu, Viorel D.; Guma, Nelson; Agaba, Hillary; Balyesiima, Godfrey; Nakami, Lydia; Stevens, Nancy J. (Frontiers in Ecology and Evolution, 2023)
Data on space-use patterns are essential for understanding species ecology and conservation. Individual chimpanzee communities are known to vary in home range size and habitat use dynamics, reflecting site-specific strategies to differences in resource availability on different landscapes. Here we present home range estimates for the Buraiga chimpanzees of Kibale National Park, Uganda, a community of eastern chimpanzees (Pan troglodytes schweinfurthii) living within the largest remaining population fragment in Uganda. The Buraiga chimpanzees are currently undergoing habituation for research and tourism under the direction of the Uganda Wildlife Authority (UWA). We analyzed 15 months of GPS data (August 2019 – March 2020, and January – July 2022), calculating overall and seasonal home range and core area estimates with two methods, minimum convex polygon (MCP) and kernel density estimates (KDE). Home range was estimated to cover an area of 15.77 km2 (95% KDE), and 24.90 km2 (100% MCP). Additionally, we found that 15.82% of the Buraiga chimpanzee’s home range overlaps with community-managed land, primarily the Kanyanchu Swamp corridor and adjacent agricultural land. Seasonally, we found that Buraiga chimpanzees used a larger area during dry season months, compared with rainy season months. Documenting how great ape populations utilize increasingly anthropogenically influenced landscapes is important in order to facilitate long-term survival in the face of climate change, habitat fragmentation, and other ongoing threats.